ANALISIS PENDAPATAN USAHATANI JAMBU METE (Anacardium Occidentale L.) DI DESA KILA, KECAMATAN AIMERE, KABUPATEN NGADA - Bernadiana Dedho Gela; Damianus Adar; Hans L Telnoni (Undana Press, 2021)
This research was conducted in Kila Village, Aimere Subdistrict, Ngada District in March to April 2018. The purpose of this study were to: (1) find out the large income of cashew farming at Desa Kila (2) knowing the size of BEP production and prices on farming Cashew nut at Kila Village (3) knows the relative advantages value of cashew farming on Kila Village. The research location was Kila Village, which was done intentionally because the location was one of the central production of cashew. Determination of respondents was done randomly, namely 10% (56 people) of the total cashew farmer population of 130 people. The results showed that the total income earned was Rp 112,417,688 with the average total income obtained from each respondent farmer in the amount of Rp 2,007,458.71. BEP Value of volume is 1.107,48 kgs with a total production of 6.255 kgs, which means that when the amount of production is 1.107,48 kg, cashew farming is in the amount of break even or the amouunt of production in return so that the total production of 6.255 kg has exceeded the break even profit. The BEP Value was Rp 3.866,76 and the average selling price was Rp 21.839,29 which means that when the cashew nut price was Rp 3.866,76/kg, the farmers has returned the capital or return of capital, so the average selling price of Rp 21.839,29 has been above the break-even price. Or in other words cashew farming was on a profitable position. The analysis results of the comparison of the revenue and cost elements of cashew farming revealed that the R/C ratio was 5,65 obtained from the total revenue of Rp 136.604.259 divided by the total cost of Rp 24.186.571. R/C Ratio of 5,65, which means that every one rupiah issued by the respondent will receive revenue of Rp 5.65 as a benefit of cashew farming activities. Because the R/C ratio was bigger than 1, it can be concluded that cashew farming was economically beneficial for farmers at the research location.